Advances in Brillouin dynamic grating in optical fibers and its applications. (January 2023) - Zhang, Hongying; Dong, Yongkang
Abstract: Brillouin dynamic gratings (BDGs) in optical fibers have been developed for more than a decade and gained considerable interests in different photonics fields. Based on its features of flexibility and all-optical generation, BDG has been explored for many applications including distributed optical fiber sensing (temperature, strain, transverse pressure, hydrostatic pressure, and salinity), all-optical signal processing, all-optical delay, microwave photonic filter, and ultrahigh resolution optical spectrometry. Especially in recent years, besides the longitudinal BDG in the backward stimulated Brillouin scattering (SBS), the transverse BDG associated with the forward SBS has been proposed for substance identification and characterization of optical fiber diameter. In this paper, a systematically theoretical analysis of BDG in optical fibers is given and its recent advances in applications is summarized.